2002
DOI: 10.1002/ecjb.10066
|View full text |Cite
|
Sign up to set email alerts
|

Gender recognition method based on silhouette, footstep, and foot pressure measurements for counting customers

Abstract: SUMMARYConventional methods of gender recognition cannot be applied to counting store customers in terms of both data acquisition conditions and processing time. To solve this problem, the authors proposed a gender recognition method based on human silhouette shape characteristics. The current study demonstrated for the first time how efficient the footstep characteristic and foot pressure characteristic are for gender recognition. It discussed the recognition technique based on joining of the mentioned charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In studying the spectral energy distributions of male and female footstep sounds, Li, Logan, and Pastore [40] found that gender was communicated by spectral peak and high frequency spectral components, affirming that frequency domain information is most important. Similar observations are also found in other research, where differences in the frequency content of the sole and heel strikes of the foot showed spectral differences between male and female walkers on a vibration sensor [56].…”
Section: Anthropometricssupporting
confidence: 91%
See 1 more Smart Citation
“…In studying the spectral energy distributions of male and female footstep sounds, Li, Logan, and Pastore [40] found that gender was communicated by spectral peak and high frequency spectral components, affirming that frequency domain information is most important. Similar observations are also found in other research, where differences in the frequency content of the sole and heel strikes of the foot showed spectral differences between male and female walkers on a vibration sensor [56].…”
Section: Anthropometricssupporting
confidence: 91%
“…In terms of a walker's gender, high frequency spectral components are commonly found to be indicative of females, whilst males tend to have greater low frequency components in their footstep sounds [40,55,56].…”
Section: Anthropometricsmentioning
confidence: 99%